ROC APP: AN APPLICATION TO UNDERSTAND ROC CURVES - VON BORRIES, George Freitas; QUADROS, Allan Vieira de Castro (Brazilian Journal of Biometrics, 2022)
We present a software application (https://gfvonborries.shinyapps.io/roc_app/) to help students understand the Receiver Operating Characteristic (ROC) curve and other concepts associated with binary classification models. We use the diagnostic test scenario as a motivation to explain the underlying concepts and the app functionalities. The ROC App enables students to interactively learn why/how the ROC curve closely relates to the accuracy rates, by seeing how these curves and rates respond to modifications on the population’s parameters.